Histone H1 Differentially Inhibits DNA Bending by Reduced and Oxidized HMGB1 Protein - Štros, Michal; Polanská, Eva; Kučírek, Martin; Pospíšilová, Šárka (PloS one, 2015)
HMGB1 protein and linker histone H1 have overlapping binding sites in the nucleosome. HMGB1 has been implicated in many DNA-dependent processes in chromatin involving binding of specific proteins, including transcription factors, to DNA sites pre-bent by HMGB1. HMGB1 can also act as an extracellular signaling molecule by promoting inflammation, tumor growth a metastasis. Many of the intra- and extracellular functions of HMGB1 depend on redox-sensitive cysteine residues of the protein. Here we report that mild oxidization of HMGB1 (and much less mutation of cysteines involved in disulphide bond formation) can severely compromise the functioning of the protein as a DNA chaperone by inhibiting its ability to unwind or bend DNA. Histone H1 (via the highly basic C-terminal domain) significantly inhibits DNA bending by the full-length HMGB1, and the inhibition is further enhanced upon oxidization of HMGB1. Interestingly, DNA bending by HMGB1 lacking the acidic C-tail (HMGB1ΔC) is much less affected by histone H1, but oxidization rendered DNA bending by HMGB1ΔC and HMGB1 equally prone for inhibition by histone H1. Possible consequences of histone H1-mediated inhibition of DNA bending by HMGB1 of different redox state for the functioning of chromatin are discussed.
Keywords: Oxidation-Reduction; Models, Molecular; Cysteine; Animals; Mutation; vazba proteinů; histony; nukleozomy; krysa rodu Rattus; superhelikální DNA; protein HMGB1; Rats; oxidace-redukce; HMGB1 Protein; zvířata; Histones; mutace; molekulární modely; Nucleosomes; Protein Binding; cystein; DNA, Superhelical